Influence of cement on concrete mix designs through sustainability indicators - Gil, Lucero (2022)
Internationally, the most widely used concrete mix design methods are the American Concrete Institute, Department of Environment, Indian Standard, Fineness Modulus and Walker. These methods propose the dosage of materials from tables and graphs developed from multiple experiments and generalize the designs to achieve optimum strength, durability, and quality performance. However, sustainability does not contemplate the design, especially cement, which is responsible for CO2 emissions and the cost of concrete. The study analyzed the procedure and dosage of five methods for a 20 MPa strength concrete mix in the laboratory and applied them to beams and columns in a multi-family building using sustainability indicators. The results indicate that the IS method uses water efficiently, is more economical, and requires less cement, while the ACI method generates a positive environmental and social impact due to the efficient consumption of materials.